Abstainers and Drinkers – Two Sides of the Same Coin?. (12th May 2023) - Raninen, Jonas; Livingston, Michael; Raitasalo, Kirsimarja; Larm, Peter; de Looze, Margaretha
Abstract: This commentary discusses a recently published literature review focussing on the growing trend of young people abstaining from drinking alcohol. Despite the recent increase in research on the decline in youth drinking, the review only identified 10 papers that explicitly examined abstainers. The inclusion criteria used thus excluded and overlooked the vast literature available on the decline in youth drinking. This commentary discusses the implications of this and raises the issue of how the adolescent abstainer should be viewed in research; is it a distinct social phenomenon with unique determinants or are abstainers merely the flip side of drinkers?